Review of impacts of biomimetic mangrove structures on wave attenuation as regenerative building strategy / Nur Raihan Fathini Zairudin, Christopher Heng Yii Sern and Zalena Abdul Aziz - Zairudin, Nur Raihan Fathini; Heng Yii Sern, Christopher; Abdul Aziz, Zalena (2022)
The increase in human population leads to the exploration and migration to urban and coastal zones, encouraging the changes in mitigating strategies for coastal protection, especially as the climate change effects exacerbate the natural environmental challenges. Currently, the mitigation strategies implemented lead to the introduction of hard and soft structures as coastal protection measures. However, integrating these hard structures has turned out to be ineffective in fully mitigating the coastal erosion issues leading to an unending chain problem. The introduction of mangroves as the soft structure remains challenging due to the time required for the establishment and uncertainties in functionality and persistence of mangroves which depends on a range of environmental conditions. Biomimicry encompasses bio-inspired approaches in developing design solutions in a sustainable paradigm while focusing on benefitting local ecology, harvesting the benefits of ecosystem services, and accommodating adaptation through regenerative ecosystems. With reference to this strategy, the study concentrates on mangroves as the basis for proposing a regenerative design solution, focusing on their dynamic and resilience properties. The proposed key element in wave attenuation and mitigating erosion is the study of hydrodynamic interaction between mangrove roots and water flow, focusing on the interactions between root porosity, water flows, and sediment transportation. Based on the literature review, the potential research gap identified is the integration of wave attenuation properties of mangrove roots into the structural design, which contributes to a regenerative building strategy, benefitting both the built environment and ecosystems.